Computerized Games and Simulations in Computer-Assisted Language Learning: A Meta-Analysis of Research - Peterson, Mark (Simulation & gaming, 2010)
This article explores research on the use of computerized games and simulations in language education. The author examined the psycholinguistic and sociocultural constructs proposed as a basis for the use of games and simulations in computer-assisted language learning. Research in this area is expanding rapidly. However, to date, few studies have critically investigated this body of work. The author reviewed key findings from influential studies. The author’s analysis reveals that, although these studies are subject to limitations, simulations and games present valuable opportunities for effective language learning. The contemporary literature on theories of language acquisition hypothesizes that simulations and games are beneficial methods for helping learners acquire another language. This article concludes by identifying potential areas for future research.